Effects of metformin on learning and memory behaviors and brain mitochondrial functions in high fat diet induced insulin resistant rats - Hiranya Pintana (2018)
Aim: Metformin is a first line drug for the treatment of type 2 diabetes mellitus (T2DM). Our previous study reported that high-fat diet (HFD) consumption caused not only peripheral and neuronal insulin resistance, but also induced brain mitochondrial dysfunction as well as learning impairment. However, the effects of metformin on learning behavior and brain mitochondrial functions in HFD-induced insulin resistant rats have never been investigated. Main methods: Thirty-two male Wistar rats were divided into two groups to receive either a normal diet (ND) or a high-fat diet (HFD) for 12 weeks. Then, rats in each group were divided into two treatment groups to receive either vehicle or metformin (15 mg/kg BW twice daily) for 21 days. All rats were tested for cognitive behaviors using the Morris water maze (MWM) test, and blood samples were collected for the determination of glucose, insulin, and malondialdehyde. At the end of the study, animals were euthanized and the brain was removed for studying brain mitochondrial function and brain oxidative stress. Key findings: We found that in the HFD group, metformin significantly attenuated the insulin resistant condition by improving metabolic parameters, decreasing peripheral and brain oxidative stress levels, and improving learning behavior, compared to the vehicle-treated group. Furthermore, metformin completely prevented brain mitochondrial dysfunction caused by long-term HFD consumption. Significance: Our findings suggest that metformin effectively improves peripheral insulin sensitivity, prevents brain mitochondrial dysfunction, and completely restores learning behavior, which were all impaired by long-term HFD consumption. © 2012 Elsevier Inc. All rights reserved.